# Rewrite in index notation

1. Sep 30, 2009

### oxxiissiixxo

w=∇×u Is this correct? w_i=ε_ijk ∂/(∂x_j ) u_k
w and u are the vectors

C=(x∙y)z Is this correct? C_i= ∑_i〖(x_i y_j)∙z_i 〗
C, x, y, z are vectors

A^T∙A ∙x=A^T∙b Is this correct? A_ij^T∙A_ij∙x_j=A_ij^T∙b_i
A is tensor and x and b are vectors

A^T is A transpose

2. Sep 30, 2009

### HallsofIvy

Assuming you are not using subscripts and superscripts to distinguish between a vector and its transpose, yes, that is correct.

3. Sep 30, 2009

### Phrak

C=(x∙y)z Is this correct? C_i= ∑_i〖(x_i y_j)∙z_i 〗
C, x, y, z are vectors

Hall is usually right on, though this one should be (assuming orthonormal coordinates)
C=(x∙y)z C_j = z_i ∑_j (x_j y_j)

4. Sep 30, 2009

### oxxiissiixxo

I want to make sure the way I am writing this A^T dot A dot x = A^T dot b in index notation correctly.

Would you mind to do that one time for me so that I can match up with my answer?

A^T dot A dot x = A^T dot b >>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>

>>>>>>>>>>>>>>> A_ij^T dot A_ij dot x_j = A_ij^T dot b_i

A_ij^T mean A_ij is a tensor with ij components and A^T mean the transpose of A
x and b are both vector

This problem was asking me to rewrite the A^T dot A dot x = A^T dot b in index notation. Thank you!

5. Sep 30, 2009

### Phrak

Just a quick hint before I knock off. The transpose of a matrix interchanges rows with columns. (A_ij)^T = A_ji.

To make the conversion to index notation it's convenient to think of the first index as indexing rows and the second as indexing columns:

C dot D = ∑_j (C_ij D_jk)

6. Sep 30, 2009

### oxxiissiixxo

Is this correct? ∑_ j A_ji dot A_ij dot x_j = ∑_ i A_ij^T dot b_i ?

7. Oct 1, 2009

### Phrak

The summation should occur between only two tensors. As you've written it, you are summing over all three on the left hand side.

I should have noticed this earlier, but you should place the dot operator only between two vectors.

U·V = UVT = ∑i Ui Vi

Vector U is multiplied with the transpose of vector V.

So we should write the expression AT·Ax as

ATAxT, where A is a matrix, ATA is a matrix, and x is a row vector.

ATA is equal to AijT multiplied by Aij, which means we are going to multiply the rows of the first matrix by the rows of the second

ATA = ∑i Aij Aij

------------------------------------------------------------------
For cut and paste.

α β γ δ ε ζ η θ ι κ λ μ ν ξ ο π ρ ς σ τ υ φ χ ψ ω . . . . . Γ Δ Θ Λ Ξ Π Σ Φ Ψ Ω
∂ ∫ ∏ ∑ . . . . . ← → ↓ ↑ ↔ . . . . . ± − · × ÷ √ . . . . . ¼ ½ ¾ ⅛ ⅜ ⅝ ⅞
∞ ° ² ³ ⁿ Å . . . . . ~ ≈ ≠ ≡ ≤ ≥ « » . . . . . † ‼

Last edited: Oct 1, 2009